Analysis of Factors which Affecting Perceived Enjoyment and Customer Continuance Intention on Mobile Games Users - Ronaldo Gultom; Boy Nurttjahyo Moch; Ramadhan Khafri; Maya Arlini Puspasari (Journal of Games, Game Art, and Gamification, 2020)
Nowadays utilization of mobile applications, especially for mobile games growth rapidly. This situation affects mobile games market more competitive and results in only few games can survive. The abundance number of mobile games that available makes users will remove their downloaded games if it lacks of interesting experience that affected their enjoyment on first try. Because of this, perceived enjoyment is often considered as an important factor that affects users’ intention to continue playing the mobile games. Therefore, this study aims to discover what factors affects perceived enjoyment and find out whether perceived enjoyment is affecting user’s intention to continue playing mobile games or not. The research model adopts several latent variables that are used to measure the perceived enjoyment and its effect on continuance intention of mobile games. The model is tested by using Partial Least Square–Structural Equation Modeling (PLS-SEM) with a sample size of 205 respondents.